2008
DOI: 10.1158/0008-5472.can-07-6052
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RET Kinase–β-Catenin Signaling Pathway Contributes to Tumorigenesis in Thyroid Carcinoma

Abstract: The RET receptor tyrosine kinase has essential roles in cell survival, differentiation, and proliferation. Oncogenic activation of RET causes the cancer syndrome multiple endocrine neoplasia type 2 (MEN 2) and is a frequent event in sporadic thyroid carcinomas. However, the molecular mechanisms underlying RET's potent transforming and mitogenic signals are still not clear. Here, we show that nuclear localization of Bcatenin is frequent in both thyroid tumors and their metastases from MEN 2 patients, suggesting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 32 publications
5
52
0
Order By: Relevance
“…Janne Balsamo and Jack Lilien and was obtained from the Development Studies Hybridoma Bank, developed by the National Institute of Child Health and Human Development, and maintained at the University of Iowa. Full-length wildtype RET, RET K758M, and GFRa1 constructs have been described previously (14). Empty vector (EV) refers to pcDNA3.1 plasmid (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Janne Balsamo and Jack Lilien and was obtained from the Development Studies Hybridoma Bank, developed by the National Institute of Child Health and Human Development, and maintained at the University of Iowa. Full-length wildtype RET, RET K758M, and GFRa1 constructs have been described previously (14). Empty vector (EV) refers to pcDNA3.1 plasmid (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cells were fixed and stained as described previously (14). Individual images were obtained with a Leica TCS-SP2 inverted microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Another dysfunctional signaling pathway identified in 65-90% of RET/PTC-positive tumors is β-catenin, which is involved in gene transcription and cell adhesion regulation (60,61). The β-catenin pathway can be directly activated by several mechanisms: via RET tyrosine residue, cAMP response element-binding (CREB), glycogen synthase kinase 3 phosphorylation (GSK3-S) or via effectors of the MAPK and PI3K pathways (61,62).…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%
“…The β-catenin pathway can be directly activated by several mechanisms: via RET tyrosine residue, cAMP response element-binding (CREB), glycogen synthase kinase 3 phosphorylation (GSK3-S) or via effectors of the MAPK and PI3K pathways (61,62). The increase in the free β-catenin protein pool promotes proliferation and invasion, possibly due to the interaction with transcriptional factors, such as the T-cell factor/ lymphoid enhancer factor (TCF/LEF), c-Myc (v-myc myelocytomatosis viral oncogene homolog), or cyclin D1 (60,61,63).…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%
“…Activated RET, including RET MEN2, can activate the Wnt pathway, that inhibits the recruitment of antigenpresenting cells (i.e., dendritic cells) (Gujral et al 2008, Castellone et al 2009, Prazeres et al 2011, Tartari et al 2011. Interestingly, it has been shown that an immune response could be elicited in MTC patients by vaccination with tumor cell-pulsed autologous dendritic cells, indicating that MTC cells display antigens that could activate antigen-presenting cells.…”
Section: Ret and Cancer Immunotherapy In Men2mentioning
confidence: 99%